Reconstructing Notary Accountability for Unilateral Amendments of Authentic Deeds in the Context of Legal Certainty and Justice - Aulia Putri Izzati; Surrahmad, Surrahmad (JURNAL USM LAW REVIEW, 2025)
This study examines notarial accountability for unilateral amendments (renvoi sepihak) to authentic deeds that undermine legal certainty and substantive justice for the parties involved. Although Articles 48–51 of the Indonesian Law on the Position of Notary (UUJN) regulate deed correction mechanisms, these provisions remain normatively vague and fail to clearly define the procedural limits regarding the timing, form, and scope of permissible amendments, thereby enabling potential abuse of authority. This research employs a normative juridical method using statutory and conceptual approaches, supported by qualitative analysis of notarial doctrines, verlijden theory, administrative intervention theory, and Supreme Court Decision Number 1003 K/Pid/2015. The findings reveal that procedural ambiguity and weak supervisory mechanisms have created a structural gap that allows unilateral alterations to authentic deeds without adequate legal safeguards. The novelty of this study lies in proposing an integrative reconstruction model of notarial accountability that combines administrative, civil, and ethical dimensions through strengthened renvoi procedures, the use of digital verification technologies, and the enhanced role of the Notary Supervisory Council. This study concludes that reconstructing the notarial accountability framework is essential to ensuring legal certainty and substantive justice in notarial practice.